Translating in Turbulent Times – Impact of the COVID-19 Pandemic Crisis on the Language Service Industry in Colombia and Spain: Perspectives to Become Sustainable. - Duro-Moreno, Miguel Jesús (IGI Global, 2022)
The language service industry was deeply impacted by the COVID-19 pandemic. The turbulent times faced because of COVID-19 changed the way LSPs made decisions and delivered services to their customers. LSPs had to react by adapting themselves to the unexpected new market game. This study scrutinizes what COVID-19 meant for the LSPs based in Colombia and Spain, and how they were tackled from those two different markets. Colombia, a developing country with an industry almost exclusively made up of independent freelance translators and interpreters, faced the crisis both distressingly and smartly. Spain, a developed country with a stronger language industry, coped with the COVID-19-induced economic calamity in a quite analogous fashion. In both cases, uncertainty led LSPs to make decisions, clarify their visions, and make a clear commitment to becoming sustainable in the global market. An in-depth analysis of how those two industries behaved might be useful to draw important conclusions on how a crisis can become an opportunity if properly managed.
Tipo de producción: capítulo de libro (revisado por pares). Posición de firma: 2. N.º total de autores: 2. Autor de correspondencia: mjduro@uma.es. Fuente de impacto: SCI 2022. Categoría: General. Índice de impacto: ICEE = 90. Revista dentro del 25%: Sí. Resultados relevantes: La editorial se halla en el segundo cuartil (concretamente, en la posición 27 de 76), con un ICEE de 90 (editoriales extranjeras). Publicación relevante: Sí. https://www.igi-global.com/about/rights-permissions/content-reuse/
Keywords: Servicios de traducción; COVID-19 - Influencia y consecuencias; Language service providers; Translation industry in Colombia; Translation industry in Spain; Impact of COVID-19 on translation